Twice Slain: Female Sex-Trade Workers and Suicide in British Columbia, 1870-1920 - Johnston, Susan (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 1994)
AbstractBetween 1870 and 1920, the voluntary deaths of 13 British Columbian women, identified by coroners and jurors as prostitutes, provoked a response out of all proportion to their numbers. This essay examines this response, focusing first on the narratives created by witnesses at the coroner's inquest on the body, and then on the interpretations of those who did not literally "know" the dead woman. I argue that the bodies of the dead can be read as a text which invoke multiple interpretations and meanings. Running through all the narratives is a discourse of respectability which shifted attention from an examination of the body and morals of one women to that of society as a whole. Those who knew the women read the death in ways that emphasized their own and the deceased's personal connection to the community in which they lived. Coroners, jurors, and the press inscribed their fears of sexual disorder and racial miscegenation upon the bodies of the dead. Through examining and responding to the deaths, the women and men involved in the inquest process helped create and bolster a particular moral and social identity which utilized the prostitute as a metaphor of social evil. When the body of the prostitute no longer evoked this response, prostitutes' deaths were excluded from the inquest process.